SIMULATION OF A PASSENGER QUEUE IN THE CUSTOMER CENTRE OF A RAILWAY OPERATOR (Perner's Contacts, 2012)
The paper describes the simulation model of a passenger queue in the customer centre of a railway operator. The simulation model is created to verify the measures used for speeding up the servicing of passengers and decreasing queue length at individual servicing points.
Keywords: simulation model, customer centre, experiment